Does effective governance matter for Islamic social finance? Evidence from mosques in Yogyakarta - Nasution, Prayudi Ibrahim; Hardiyanti, Wida Reza; Sambodo, Novat Pugo; Pailis, Eka Armas (Faculty of Economics, Universitas Islam Indonesia, 2026)
Purpose – This paper examines how effective governance influences Islamic social finance management, using mosques in Yogyakarta as a case study during and after the Covid-19 crisis. Methodology – This study employs a survey with a sample of 360 mosques in Yogyakarta using a quantitative approach with ordinary least squares (OLS) and logit regression models. Findings – The findings indicate that an increase in the effective governance index score has a positive and significant effect on the fundraising index and zakat distribution, resulting in increases of 0.14 standard deviations and 6.5 percent, respectively. Furthermore, effective governance had a positive and significant effect on the probability of mosques having a financial management system, with a marginal effect of 7.3 poin percentage.Implication – The government should offer financial management training and support the digitalization of reporting systems as a means of strengthening mosque governance.Limitations – First, the data used were cross-sectional, which may restrict researchers' ability to identify long-term causal relationships. Second, despite efforts to address endogeneity using several variables, the instruments are theoretically valid but statistically insignificant. Original – This study is the first to present micro-level empirical evidence from mosques in Yogyakarta, an area that has rarely been explored in Islamic financial governance literature. Furthermore, we used a multidimensional effective governance index that ranges from 0 to 1. The index was then standardized using a z-score to ensure comparability and balance across mosques.